2016
DOI: 10.1177/1533034616630866
|View full text |Cite
|
Sign up to set email alerts
|

miR-139 Functions as An Antioncomir to Repress Glioma Progression Through Targeting IGF-1 R, AMY-1, and PGC-1β

Abstract: Gliomas are the most common primary malignant brain tumor with poor prognosis, characterized by a highly heterogeneous cell population, extensive proliferation, and migration. A lot of molecular mechanisms regulate gliomas development and invasion, including abnormal expression of oncogenes and variation of epigenetic modification. MicroRNAs could affect cell growth and functions. Several reports have demonstrated that miR-139 plays multifunctions in kinds of solid tumors through different pathways. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 43 publications
(50 reference statements)
1
28
0
Order By: Relevance
“…Jung and Kim (15) reported that the upregulation of MYCBP in colon carcinoma cells may have co-activating effects on MYC. Wang et al (20) reported that MYCBP regulated multiple biological processes within glioma cells, which is associated with malignant characteristics, including cancer cell proliferation, transformation and metastasis. Additionally, Furusawa et al (24) suggested that MYCBP is a trigger in the tumorigenesis of chronic myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jung and Kim (15) reported that the upregulation of MYCBP in colon carcinoma cells may have co-activating effects on MYC. Wang et al (20) reported that MYCBP regulated multiple biological processes within glioma cells, which is associated with malignant characteristics, including cancer cell proliferation, transformation and metastasis. Additionally, Furusawa et al (24) suggested that MYCBP is a trigger in the tumorigenesis of chronic myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of MYC has been suggested to serve key roles in cell migration and invasion by promoting the expression of target genes (26). Previous studies have been performed to inhibit the expression of MYCBP, and thus the MYC pathway, and observe the resultant inhibition of cancer cell migration and invasion (20,27). Furthermore, the overexpression of MYCBP facilitated Hedgehog signaling responses, whereas the knockdown of MYCBP compromised Hedgehog signaling responses (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-378-and miR-378*-deficient mice are resistant to HFD-induced obesity and exhibit increased mitochondrial fatty acid metabolism (54). Second, PGC-1b is a direct target of miR-139 and may be involved in the development and progression of glioma cells (55). We also found that in response to OA treatment, miR-98-5p inhibited PGC-1b mRNA expression in the liver.…”
Section: Discussionmentioning
confidence: 64%
“…Some miRNAs promoted gliomas development, which were considered as biomarkers for earlier diagnosis 16 . While another group of miRNAs functioned as anti-tumor genes and predicted better prognosis, such as miR-139, miR-124 and miR-34 [17][18][19] . Therefore identification glioma-related miRNAs and elucidation their effects and regulatory mechanisms have important roles in gliomas therapy.…”
mentioning
confidence: 99%